2011
DOI: 10.1007/s12011-011-9089-7
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Iodine Deficiency and Hypothyroidism Impair Neural Development, Upregulate Caveolin-1, and Downregulate Synaptotagmin-1 in the Rat Cerebellum

Abstract: Adequate thyroid hormone is critical for cerebellar development. Developmental hypothyroidism induced by iodine deficiency during gestation and postnatal period results in permanent impairments of cerebellar development with an unclear mechanism. In the present study, we implicate cerebellar caveolin-1 and synaptotagmin-1, the two important molecules involved in neuronal development, in developmental iodine deficiency, and in developmental hypothyroidism. Two developmental rat models were created by administra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Nissl staining was performed with paraffin sections. Stained cells with round and palely stained nuclei were considered to be surviving cells, whereas shrunken cells with pyknotic nuclei were considered to be nonsurviving cells as described previously42. Immunohistochemistries with polyclonal antibodies against c-Ret protein (1:100; Immuno Biological Laboratories), phosphorylated c-Ret Y1062 (1:100; Abcam) and phosphorylated NF-κB p50 (1:50; Santa Cruz) were performed for frozen sections with Can Get Signal immunostaining solution (TOYOBO).…”
Section: Methodsmentioning
confidence: 99%
“…Nissl staining was performed with paraffin sections. Stained cells with round and palely stained nuclei were considered to be surviving cells, whereas shrunken cells with pyknotic nuclei were considered to be nonsurviving cells as described previously42. Immunohistochemistries with polyclonal antibodies against c-Ret protein (1:100; Immuno Biological Laboratories), phosphorylated c-Ret Y1062 (1:100; Abcam) and phosphorylated NF-κB p50 (1:50; Santa Cruz) were performed for frozen sections with Can Get Signal immunostaining solution (TOYOBO).…”
Section: Methodsmentioning
confidence: 99%
“…It has been demonstrated that thyroid dysfunction affected synaptic proteins in adult rats [26]. Thyroid hormone deficiency resulted in the down-regulation of syt-1 expression in rat hippocampus [25,27] and cerebellum [28], and the impairment in hippocampal-dependent tasks of learning and memory [29]. These findings emphasized a close relationship between thyroid dysfunction and syt-1.…”
Section: Animal Model Of Schmentioning
confidence: 95%
“…Brain damage is mainly found in the prefrontal, hippocampus and cerebellar cortex 5 . This is caused by cell propagation disorders (proliferation), cell migration, cell differentiation, and decreases in synapses formation, myelin formation, neuron growth, neurotransmitter formation, and increased cell death and astrocytic proliferation, and consequently the connectivity between neurons perfect 6 . Connectivity between parts of the brain is an essential requirement for cognitive function 6 .…”
Section: Introductionmentioning
confidence: 99%
“…This is caused by cell propagation disorders (proliferation), cell migration, cell differentiation, and decreases in synapses formation, myelin formation, neuron growth, neurotransmitter formation, and increased cell death and astrocytic proliferation, and consequently the connectivity between neurons perfect 6 . Connectivity between parts of the brain is an essential requirement for cognitive function 6 . In addition, hypothyroidism can also cause mental retardation, and decreases speech and hearing ability and motor impairment.…”
Section: Introductionmentioning
confidence: 99%